ANALISIS PERLAKUAN AKUNTANSI PERSEDIAAN BERDASARKAN PSAK NO. 14 PADA PT. MODERNA TEHNIK PERKASA - Sheva Rajaby Eliya Trenggono; Rida Perwita Sari (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This study aims to assess the suitability of recording and measuring inventory of PT Moderna Tehnik Perkasa, a construction services company in East Java, with PSAK No. 14. Inventory is an important asset for the continuity of company operations, but it is often difficult to record and value accurately. Using a qualitative descriptive method, this study analyzes data through a process of decomposing, describing, and comparing. The results reveal that PT Moderna Tehnik Perkasa has implemented the rules of PSAK No. 14 in its inventory management, demonstrating compliance with applicable accounting standards.